From Community Policing to Political Police in Nicaragua [de Policía Comunitaria a Policía Política en Nicaragua] - Dammert-Guardia, L (Centre for Latin American Research and Documentation/Centro de Estudios y DocumentaciÃ³n Latinoamericanos (CEDLA), 2020)
In a region plagued by high rates of violent crime and repressive policing practices, Nicaragua has earned a reputation as exceptional. Despite poverty, inequality, and a historical legacy of political violence and repression, Nicaragua has defied regional trends. It has registered low rates of violent crime while deploying policing practices that emphasized prevention over repression. April 2018 marked an end to this exceptionalism. Police attacked anti-government protestors, and launched a sustained campaign against dissidents that continues to the present day. While the Nicaraguan police had long cultivated a reputation as community-oriented and non-repressive, they appeared to quickly change into a repressive, political force. In this paper, we trace how the Nicaraguan police have evolved over time. Relying upon longitudinal data from 1996-2019 from the Latin American Public Opinion Project, we trace the process of police reform in Nicaragua, and analyse public attitudes towards the police as these reforms unfolded. Keywords: Nicaragua, community policing, police reform, public trust, crime. © Lucía Dammert, Mary Fran T. Malone. Open Access article distributed under the terms of the Creative Commons Attribution 4.0 Unported (CC BY 4.0) License https://creativecommons.org/licenses/by/4.0/.